PyRamanGUI: Open-source graphical user interface for analyzing Raman spectra - Simon Brehm; Cameliu Himcinschi; Jakob Kraus; Jens Kortus (SoftwareX, 2023)
With PyRamanGUI, we present a versatile tool to analyze Raman spectra. The program is constructed as a graphical user interface, so no knowledge in coding is required for its use. The source code is completely written in Python and freely available (https://gitlab.com/brehmsi/PyRamanGUI). PyRamanGUI combines common analysis methods like peak fitting, baseline correction, and smoothing with the organization of Raman data in projects and the plotting of spectra.